Novel insights into genetic characteristics of blaGES-encoding plasmids from hospital sewage - Ota, Yusuke; Prah, Isaac; Mahazu, Samiratu; Gu, Yoshiaki; Nukui, Yoko; Koike, Ryuji; Saito, Ryoichi (Frontiers in Microbiology, 2023)
Introduction: The prevalence of Guiana extended-spectrum (GES)-type carbapenemase producers is increasing worldwide, and hospital water environments are considered as potential reservoirs. However, the genetic features underlying this resistance are not yet fully understood. This study aimed to characterize blaGES-encoding plasmids from a single-hospital sewage sample in Japan. Methods: Carbapenemase producers were screened using carbapenemase-selective agar and polymerase chain reaction. Whole-genome sequencing analyses were performed on the carbapenemase-producing isolates. Results: Eleven gram-negative bacteria (four Enterobacter spp., three Klebsiella spp., three Aeromonas spp., and one Serratia spp.) with blaGES-24 (n=6), blaGES-6 (n=4), and blaGES-5 (n=1) were isolated from the sewage sample. Five blaGES-24 and a blaGES-5 were localized in IncP-6 plasmids, whereas three blaGES-6 plasmids were localized in IncC plasmids with IncF-like regions. The remaining blaGES-6 and blaGES-24 were respectively localized on IncFIB-containing plasmids with IncF-like regions and a plasmid with an IncW-like replication protein. The IncP-6 and IncW-like plasmids had a close genetic relationship with plasmids from Japan, whereas the IncC/IncF-like and IncFIB/IncF-like plasmids were closely related to those from the United States and Europe. All blaGES genes were located on the class 1 integron cassette of the Tn3 transposon-related region, and the IncC/IncF-like plasmid carried two copies of the integron cassette. Eight of the eleven blaGES-encoding plasmids contained toxin-antitoxin system genes. Discussion: The findings on the plasmids and the novel genetic content from a single wastewater sample extend our understanding regarding the diversity of resistance and the associated spread of blaGES, suggesting their high adaptability to hospital effluents. These findings highlight the need for the continuous monitoring of environmental GES-type carbapenemase producers to control their dissemination.